The Effects of Diet Induced Obesity (DIO) on Skeletal Muscle Transcription in MuRF1 KO Mice - Marshall, Andrea Gail (J Endocr Soc, 2021)
Background: As obesity and Type II Diabetes rise globally, it is important to understand the similarities and differences in the response of metabolic tissues between males and females. We wanted to evaluate the impact of prolonged diet induced obesity (DIO) on the skeletal muscle transcriptome of our MuRF1 KO (KO) mice. Methods: RNA was isolated from the gastrocnemius muscle of male and female WT and KO mice that were fed either standard chow (Envigo 2918) or a 45% HFD (Research Diets D12451) for 22 weeks (n = 4). RNA was enriched for mRNA prior to library preparation. RNA sequencing was performed using 150 bp paired-end reads (~ 31.6 M reads per sample). Differentially expressed genes (DEGs) were identified using DESeq2 with an FDR set to 5%. Results: At baseline (chow diet), both male and female KO mice had DEGs compared to their WT counterparts (male, 1174; female, 105). Most DEGs were found to be unique by sex (male, 1151; female, 82), though 23 genes were found to be changed in common. After obesity was induced by 22 weeks of 45% HFD feeding, KO animals showed a greater transcriptional response than their WT counterparts. Males had 1821 DEGs (v. 179 in WT) while females had 4425 DEGs (v. 2090 in WT). In males, 78 genes were changed in common between WT and KO in response to DIO, with 76 of those genes changing in the same direction (Slc282a and Gm15427 did not). In females, 1445 genes were changed in common between WT and KO, with all but 2 genes (Pla2g7 and Zfp385b) changing in the same direction. In both male and female KO animals, oxidative phosphorylation and ribosomal pathways were most significant, though the direction of change in the DEGs was opposite. Conclusion: In skeletal muscle, sex highly influences the genes and pathways changed in response to DIO. Even among common pathways identified, the response between males and females differed. Loss of MuRF1 results in common and unique transcript changes in and between males and females under normal conditions and in DIO.